Hypogonadism as a Reversible Cause of Torsades de Pointes in Men. Issue 1 (3rd July 2018) - Salem, Joe-Elie; Waintraub, Xavier; Courtillot, Carine; Shaffer, Christian M.; Gandjbakhch, Estelle; Maupain, Carole; Moslehi, Javid J.; Badilini, Fabio; Haroche, Julien; Gougis, Paul; Fressart, Veronique; Glazer, Andrew M.; et al.
Abstract : Supplemental Digital Content is available in the text.